The six-minute walking test in dogs at high altitude - Vargas-Pinto, Pedro (2019)
The six-minute walking test is a diagnostic and prognostic tool widely used in human medicine. However, to date there is no enough evidence in veterinary medicine to support its use in the same way. This study was conducted at 2600 meters above the sea level and included only healthy, young and acclimated dogs to generate averaged distances walked and to evaluate the impact of this test on some physiological variables. Distances walked were no very different to the average reported in other studies at the sea level. Nevertheless, a physiological variable such as heart rate had a different response. No comparable data in respiratory rate was found. The six-minute walk test is a repeatable test that can be used safely and reliably in canines at high-altitude so that it can be used as a prognostic test in the practice of small animals. This study aims to be the base for future attempts to establish the comparison with chronically sick dogs and the potential use of this test as a prognostic tool in small animal practice.